2014
DOI: 10.1037/a0034943
|View full text |Cite
|
Sign up to set email alerts
|

The association of therapist empathy and synchrony in vocally encoded arousal.

Abstract: Empathy is a critical ingredient in motivational interviewing (MI) and in psychotherapy generally. It is typically defined as the ability to experience and understand the feelings of another. Basic science indicates that empathy is related to the development of synchrony in dyads. However, in clinical research, empathy has proved difficult to operationalize and measure, and has mostly relied on the felt sense of observers, clients, or therapists. We extracted estimates of therapist and standardized patient (SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
165
4
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(176 citation statements)
references
References 54 publications
(69 reference statements)
4
165
4
3
Order By: Relevance
“…anxiety, distress) can be identified as they are associated with higher f0 within the speaker's vocal range and context [16,26]. Furthermore, f0 is an advantage over other behavioural signals, as it is a nonintrusive tool and extracting vocal arousal can assess therapist's empathy through their relational pitch [22] [23]. A systematic search of 'Web of Science' and 'PubMed' databases demonstrated that f0 has never been used in oncology before.…”
Section: Fundamental Frequency Of Pitch (F0)mentioning
confidence: 99%
See 2 more Smart Citations
“…anxiety, distress) can be identified as they are associated with higher f0 within the speaker's vocal range and context [16,26]. Furthermore, f0 is an advantage over other behavioural signals, as it is a nonintrusive tool and extracting vocal arousal can assess therapist's empathy through their relational pitch [22] [23]. A systematic search of 'Web of Science' and 'PubMed' databases demonstrated that f0 has never been used in oncology before.…”
Section: Fundamental Frequency Of Pitch (F0)mentioning
confidence: 99%
“…One of the current goals of behavioural signal processing (BSP) is to combine human and machine observations of dyadic interactions to develop computational models that can assess social, emotional, and communicative states of interlocutors in great detail [21]. Beginning to integrate and test the applicability of these approaches to the study of health communication could therefore lead to great benefits, particularly when studying the vocal properties of empathy [22,23] Kirshnan and Fernandez's methods for recognising emotional states from speech indicate the importance of f0 (U.S. Patent No. 8,595,005 B2, 2013) [24].…”
Section: Fundamental Frequency Of Pitch (F0)mentioning
confidence: 99%
See 1 more Smart Citation
“…the perception that a therapist is wholly engaged in and attuned with and for the client. Imel et al (2014) found strong evidence for vocal synchrony in clinical dyads, as well as an association between synchrony and client empathy ratings. On the basis of these observations, they suggested that synchrony in physiological arousal could be mediated in part via vocal cues.…”
Section: The Present Study Is Part Of a Research Project Called The Rmentioning
confidence: 96%
“…Given the evidence underlining the importance of empathic communication in psychotherapy (e.g. Elliott, Bohart, Watson, and Greenberg, 2011) and the role of non-verbal aspects (Imel et al, 2014;Weiste and Peräkylä, 2014), we anticipated that soft prosody would be a prominent feature of expressions of affiliation. It appeared that soft prosody did indeed have a role in how the therapist and student showed affiliation with the weeping client.…”
Section: Discussionmentioning
confidence: 99%